2014
DOI: 10.1007/s10803-014-2271-y
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Strategies to Elicit Autobiographical Memories in Autism Spectrum Disorders, Developmental Language Disorders and Typically Developing Children

Abstract: Conversations about the past support the development of autobiographical memory. Parents’ strategies to elicit child's participation and recall during past event conversations were compared across three school-age diagnostic groups: autism spectrum disorder (ASD, n = 11), developmental language disorders (n = 11) and typically developing (TD, n = 11). We focused on the prevalence of directives versus enrichment of events. Groups did not differ in number of events, length, and total turns. However, parents of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…59(p.506) What sparse literature is available on the topic suggests that parents adopt a more directive and less elaborative reminiscing style when interacting with their children with ASD. 60 Although such adjustments may help the child verbalize more accurate recollections (a laudable goal for children with ASD who are known to be less detailed and accurate in reports of past experience), they may not be optimal for supporting the development of memory in a truly episodic way. Goldman and DeNigris suggested that parents of children with ASD may have a "greater emphasis on external, objective and factual elements of the experience" and may adopt a conversational style that "more closely resembles an interview than a natural dialogue."…”
Section: Why Elaborative Reminiscing Is Criticalmentioning
confidence: 99%
See 1 more Smart Citation
“…59(p.506) What sparse literature is available on the topic suggests that parents adopt a more directive and less elaborative reminiscing style when interacting with their children with ASD. 60 Although such adjustments may help the child verbalize more accurate recollections (a laudable goal for children with ASD who are known to be less detailed and accurate in reports of past experience), they may not be optimal for supporting the development of memory in a truly episodic way. Goldman and DeNigris suggested that parents of children with ASD may have a "greater emphasis on external, objective and factual elements of the experience" and may adopt a conversational style that "more closely resembles an interview than a natural dialogue."…”
Section: Why Elaborative Reminiscing Is Criticalmentioning
confidence: 99%
“…Yet, the manner in which this is done is crucially important in light of the previous finding that caregivers of children with ASD may focus on accuracy at the expense of an elaborative style whose goal is to construct a shared experience. 60 For the time being, we recommend that adult interlocutors issue gentle content corrections while adding information to the ongoing dialogue (e.g., child: "Sam was at the beach"; adult: "Sam wasn't at the beach. Remember, he couldn't come because he had a soccer game.…”
Section: Why Elaborative Reminiscing Is Criticalmentioning
confidence: 99%
“…Previous research has suggested that such information is retrieved from episodic memory and that this is impaired in individuals with ASD (Boucher & Mayes, 2011;Bowler et al, 2011). Goldman and DeNigris (2015) noted that parents of schoolage children with ASD engaged in more structured reminiscing than did parents of typically developing children. The reminiscing was not coconstructed.…”
Section: Asdmentioning
confidence: 99%
“…The parents engaged in role-play using transcripts of narrative conversations produced by individuals with ASD and by individuals with TD, which helped them to recognize the existing communicative gaps of this particular population. Because of prior research documenting difficulties that parents of individuals on the spectrum present in reminiscing with their children (Goldman & DeNigris, 2015), parents were not advised to encourage other family members who were not present for the training session to use these methods and strategies.…”
Section: Methodsmentioning
confidence: 99%
“…BAP features in parents may influence how they interact with their children, and there is some evidence to suggest parent BAP status is a potential moderator of the impact of parent-mediated interventions (Parr, Gray, Wighamn, McConachie, & LeCouteur, 2015). Goldman and DeNigris (2015) compared parents’ strategies for eliciting children’s participation in talk about the past across three groups of 11-year-olds: children with ASD, children with developmental language disorders, and children with TD. Those authors found that parents of children with ASD, to maximize interactions, produced more direct questions, corrections, and unrelated turns than parents of children with TD.…”
mentioning
confidence: 99%